Comparison of artificially weathered Macondo oil with field samples and evidence that weathering does not increase environmental acute toxicity. (May 2020) - Faksness, Liv-Guri; Altin, Dag; Størseth, Trond R.; Nordtug, Trond; Hansen, Bjørn Henrik
Abstract: Macondo source oils and artificially weathered oil residues from 150 °C+ to 300 °C+, including artificially photo oxidized oils, were prepared and used for generating low energy water accommodated fractions (LE-WAFs) in order to assess the impact of oil weathering on WAF chemistry composition and toxicity to marine organisms. Two pelagic species representing primary producers (the marine algae Skeletonema pseudocostatum ) and invertebrates (the marine copepod Acartia tonsa ) were tested. Obtained acute toxicity levels, expressed as EC/LC50 values, were in the same range or above the obtained maximum WAF concentrations for WAFs from most weathering degrees. Based on % WAF dilutions, reduced toxicity was determined as a function of weathering. The chemical compositions of all WAFs were compared to compositions obtained from water samples reported in the GRIIDC database using multivariate analysis, indicating that WAFs of photo oxidized and two field weathered oils resembled the field data the most. Highlights: Chemistry and acute toxicity in WAFs from fresh and artificially weathered DWH oils. Acute toxicity tests using S. costatum (algae) and A. tonsa (copepod) performed. Solubility and maximum WAF concentration decrease during the weathering process. All EC50 and LC50s were at or above the maximum total WAF concentration tested. The EC10 and LC10 values decreased with increased weathering.